Design Web-Based and Mobile Application Doctor Reservation Using Laravel Framework at Clinic Valio Centre - Dava Alhaq Nur Addin; Arief Hermawan (Politeknik Piksi Ganesha Indonesia, 2024)
Valio Medical Center Clinic, Central Lombok, faces a significant problem with the length of time patients wait to get a doctor's service, often exceeding the 60-minute standard set by the Ministry of Health. This research aims to solve the problem by developing a web-based and mobile Doctor Reservation Application using the Laravel framework. The method used is the creation of a doctor's registration system through web and mobile media with Laravel, which is built with the Model View Controller (MVC) concept. The results showed that the application developed using Laravel can run well and effectively reduce patient waiting time at Valio Medical Center. Design a doctor reservation system that facilitates users to make doctor reservations without having to come directly to the hospital, with an easy-to-use web-based and mobile interface, using the Laravel framework.